Yusif Ziya Talibzade’s Views on Islamism and Turkish-Islamic Unity - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2022)
The article shows that Akhund Yusif Zia Talibzade’s views on Islamism and Turkish-Islamic unity were significant in the twentieth century. Yusuf Ziya’s devotion to Islamism and the Turkish-Islamic unity was based on the problems of the Persianization of the Azerbaijanis and Russification policy of the Tsarist Russia. That is, the Persianization of the Azerbaijani people under the name of the Shiite sect, and the Russification of the other part under the influence of social democracy, both played important roles in shaping Y.Z. Talibzade’s views on Islamism and Turkish-Islamic unity. Islamism was especially influential in the early days of the struggle against tsarist Russia, and Talibzade had interpretations and opinions about it. Yusif Ziya, who approached the national issue from a religious standpoint in the beginning, believed that the Islamic religion is the foundation of nations. The article also includes Y.Z. Talibzade’s criticism of perspectives of Western nations on the cultural and ideological situation in Islamic world. Yusif Ziya attempted to explain Western thinkers’ erroneous position on the Islamic religion. Yusif Ziya’s views on Turkish-Islamic unity, as well as TurkismTuranism, were discussed in the article. The Ottoman Empire was the foundation for the development of the Turkish-Islamic world and TurkishIslamic unity, as demonstrated here. His service in the Ottoman army, in particular, strengthened his belief in Turkish-Islamic unity during the years 1910-1918, when the Ottoman army first occupied the Balkans and then the First World War. In general, the article explains why Yusif Ziya was more committed to the idea of Turkish-Islamic unity and was hesitant to establish independent Turkish states. The influence of Anwar Pasha, in particular, on his commitment to the idea of Turkish-Islamic unity, or his desire for a unified Turkish-Islamic state, has been thoroughly explained. In general, Yusif Ziya saw a Turkish-Islamic union based on the Islamic religion as the future of all Muslim-Turkish peoples, including the people of Azerbaijan. He was later recognized as a pan-Islamist and pan-Turkist intellectual, social, and political figure from this perspective.